Physical, psychological and pandemic fatigue in the fourth wave of COVID-19 outbreak in Hong Kong: population-based, cross-sectional study - Elsie Yan; Haze K L Ng; Daniel W L Lai; Vincent W P Lee (BMJ Open)
Objectives To examine the physical, psychological and pandemic fatigue during the COVID-19 pandemic, and to explore the correlates of fatigue using a representative, population-based, community sample of Chinese adults in Hong Kong.Design Cross-sectional study.Setting Telephone surveys in Hong Kong from December 2020 to January 2021 (during the fourth wave of COVID-19 outbreak).Participants 1255 adults living in Hong Kong aged 18 years or older sampled using a multistage approach (53% women).Main outcome measures Physical and psychological fatigue: The Fatigue Assessment Scale (with a cut-off score of 22). Pandemic fatigue: Adherence to six disease prevention measures (DPM) recommended by the government.Results About 25.7% of the participants were feeling fatigued physically and psychologically. Physical and psychological fatigue was not directly associated with pandemic fatigue, and their association was fully mediated by self-perceived disruptions of COVID-19-related restrictions in daily life. Results from the hierarchical regression analysis showed that higher levels of fatigue were associated with economically inactive status (B=0.18, SE=0.04, p<0.001), having family or friend infected with COVID-19 before or during the study (B=0.17, SE=0.01, p<0.001), lower acceptability of DPM (B=−0.16, SE=0.03, p<0.001), greater disruptions in daily life (B=0.22, SE=0.02, p<0.001), and greater trust in authorities in ending the pandemic (B=0.11, SE=0.02, p<0.001).Conclusions Fatigue affected many individuals during the pandemic. Disruptions of DPM in daily life may serve as a mediator in the association between pandemic fatigue and physical and psychological fatigue, reflecting the need of effective interventions to reduce self-perceived disruptions of COVID-19-related restrictions in the general population. Resources should be allocated to provide sufficient services to individuals vulnerable to fatigue during the prolonged pandemic.